2017
DOI: 10.1515/ijame-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Buckling Load of Circular and Corrugated Tubes by Utilizing Key Performance Indicators

Abstract: The performance of buckling load of tubular structures under quasi-static axial loading is quite appreciable, numerous tubes of various cross-section have been extensively investigated and corrugated sections have been designed to further improve the performance. In this paper, a carefully designed set of key performance indicators (KPIs) is utilized to assess and compare the buckling load of circular and corrugated tubes. A series of diagrams related to KPIs with various parameters of tubes are presented to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Corrugated structures show exceedingly anisotropic behavior and high stiffness transverse to the corrugation direction [15]. The influence of the degree of amplitude and wavelength of corrugated tubes on energy absorption (EA) and peak crushing force(PCF) was reported by Sharad Rawat et al [16].The previous study reveals that buckling load can be easily enhanced by changing cross-section from circular to corrugated [17].The avail of using corrugated cross section is that with a slight increase in weight there is a significant rise in peak force and energy absorption over comparable tubular sections. In the present work, the crushing behavior and the energy absorption of corrugated and circular tubes under quasi-static axial loading were investigated numerically.…”
Section: Introductionmentioning
confidence: 94%
“…Corrugated structures show exceedingly anisotropic behavior and high stiffness transverse to the corrugation direction [15]. The influence of the degree of amplitude and wavelength of corrugated tubes on energy absorption (EA) and peak crushing force(PCF) was reported by Sharad Rawat et al [16].The previous study reveals that buckling load can be easily enhanced by changing cross-section from circular to corrugated [17].The avail of using corrugated cross section is that with a slight increase in weight there is a significant rise in peak force and energy absorption over comparable tubular sections. In the present work, the crushing behavior and the energy absorption of corrugated and circular tubes under quasi-static axial loading were investigated numerically.…”
Section: Introductionmentioning
confidence: 94%
“…1 shows the hollow corrugated column with sinusoidal pattern used in the present paper. Since it is found that corrugation makes the structure more strength along the length of the column [7] as compared to conventional circular hollow columns. As buckling is the most important phenomenon as a result of axial-compression forces.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that by increasing the number of corners of polygon its energy absorbing capacity also increases but to a certain extent [6]. The previous study shows that the buckling load was of the thin-walled metallic tubes were increased when the cross sections were combined [7] and corrugation was introduced [8]. In addition to these, metallic honeycomb is also used widely as an extension for its high energy dissipating mechanism and an excellent strength to mass ratio.…”
Section: Introductionmentioning
confidence: 99%